2011
DOI: 10.2147/idr.s4188
|View full text |Cite
|
Sign up to set email alerts
|

Safety and efficacy of entecavir for the treatment of chronic hepatitis B

Abstract: Entecavir is a cyclopentyl deoxyguanosine analog that was approved for the treatment of the hepatitis B virus (HBV) in 2005. In Phase III trials, it showed potent HBV suppression with drops of 6- to 7-log copies/mL in HBV DNA at 1 year. In addition, rates of genotypic resistance in nucleos(t)ide-naïve patients are low, reaching only 1.2% after 6 years. Safety and efficacy have been established in compensated cirrhosis and HIV-coinfected patients. Studies in decompensated cirrhosis also show efficacy. Because o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 68 publications
1
21
0
Order By: Relevance
“…The rtM204V/I mutation, lamivudine's signature mutation, is necessary but not sufficient for entecavirresistance, causing an 8-to 10-fold decrease in susceptibility to entecavir compared with wild-type HBV. Other mutations at positions rtT184, rtS202, and rtM250 confer additional decreases in entecavir susceptibility [25,27,28]. In the present study, two patients (Patients #3 and 5) with mutations at position rtM204V/I, without rtT184, rtS202, or rtM250 mutations, showed emergence of VBT, as did one patient (Patient #4) with an rtA181T mutation, which was first reported in a LAM-treated patient [29].…”
Section: Discussionsupporting
confidence: 69%
“…The rtM204V/I mutation, lamivudine's signature mutation, is necessary but not sufficient for entecavirresistance, causing an 8-to 10-fold decrease in susceptibility to entecavir compared with wild-type HBV. Other mutations at positions rtT184, rtS202, and rtM250 confer additional decreases in entecavir susceptibility [25,27,28]. In the present study, two patients (Patients #3 and 5) with mutations at position rtM204V/I, without rtT184, rtS202, or rtM250 mutations, showed emergence of VBT, as did one patient (Patient #4) with an rtA181T mutation, which was first reported in a LAM-treated patient [29].…”
Section: Discussionsupporting
confidence: 69%
“…Compared with other available nucleos(t)ide analogs, ETV achieves more potent HBV DNA suppression than all agents except perhaps TDF, which is equivalent 12. Our previous study 13 has shown that ETV had better rate of virologic response, lower incidence of resistance, commensurable safety as well as seroconversion rate when compared to LAM, ADV, LdT.…”
Section: Discussionmentioning
confidence: 94%
“…It blocks HBV replication by inhibiting HBV polymerase, the DNA strand via reverse transcription elongation, and Ye XG et al . Entecavir and lamivudine for HBV cirrhosis Removing the inferior quality trials [13,15,17] DNA-dependent plus-strand DNA synthesis [25] . ETV has the advantage of a higher rate of HBV DNA suppression, low drug-resistance and high safety, especially in LAM-resistant CHB patients [26] .…”
Section: Discussionmentioning
confidence: 99%